The seventh veil of salome eaudiobook - Moreno-Garcia, Silvia (Books on Tape, 2024)
GOOD MORNING AMERICA BOOK CLUB PICK • A young woman wins the role of a lifetime in a film about a legendary heroine—but the real drama is behind the scenes in this sumptuous historical epic from the New York Times bestselling author of Mexican Gothic . “Whenever I want to read a book I know will be good, I go to Silvia Moreno-Garcia.”—Taylor Jenkins Reid, author of The Seven Husbands of Evelyn Hugo A BEST BOOK OF THE YEAR: The Washington Post, NPR, BookPage, CrimeReads 1950s Hollywood: Every actress wants to play Salome, the star-making role in a big-budget movie about the legendary woman whose story has inspired artists since ancient times. So when the film’s mercurial director casts Vera Larios, an unknown Mexican ingenue, in the lead role, she quickly becomes the talk of the town. Vera also becomes an object of envy for Nancy Hartley, a bit player whose career has stalled and who will do anything to win the fame she believes she richly deserves. Two actresses, both determined to make it to the top in Golden Age Hollywood—a city overflowing with gossip, scandal, and intrigue—make for a sizzling combination. But this is the tale of three women, for it is also the story of the princess Salome herself, consumed with desire for the fiery prophet who foretells the doom of her stepfather, Herod: a woman torn between the decree of duty and the yearning of her heart. Before the curtain comes down, there will be tears and tragedy aplenty in this sexy Technicolor saga.